2023
DOI: 10.3168/jdsc.2022-0283
|View full text |Cite
|
Sign up to set email alerts
|

Associations of antral follicle count with fertility in cattle: A review

Abstract: Graphical Abstract Summary: Ultrasonic determination of antral follicle count (AFC) is used to classify animals into high or low AFC categories. These categories have a wide range and animals classified as low on one study may be considered high by another study based on the population. Associations with high AFC cows include greater follicular vasculature, blastocyst rates, hatched blastocyst rates, 12-d embryonic cell growth and cleavage rates, along with a lower number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The AFC values obtained from this study surpass those reported by Cushman et al (2014) (21.4) and Grigoletto et al (2020) (12.49) in their respective evaluations of Angus and Nellore heifers. It is crucial to underscore that numerous intrinsic factors tied to animal physiology, such as breed differences between Bos taurus and Bos indicus (Alward et al, 2023), the phase of the estrous cycle (Ireland et al, 2008), age (Burns et al, 2005), body condition (Moraes et al, 2019), nutritional status (Cushman et al, 2014), and individual genetic variability, can influence these results.…”
Section: Resultsmentioning
confidence: 99%
“…The AFC values obtained from this study surpass those reported by Cushman et al (2014) (21.4) and Grigoletto et al (2020) (12.49) in their respective evaluations of Angus and Nellore heifers. It is crucial to underscore that numerous intrinsic factors tied to animal physiology, such as breed differences between Bos taurus and Bos indicus (Alward et al, 2023), the phase of the estrous cycle (Ireland et al, 2008), age (Burns et al, 2005), body condition (Moraes et al, 2019), nutritional status (Cushman et al, 2014), and individual genetic variability, can influence these results.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the prostaglandinendoperoxide synthase 1 gene (PTSGS1), which is associated with AMH, was also positively correlated with ovulation, NCE and NTE (Gobikrushanth et al 2018;Jaton et al 2016). Similarly, SNPs and genes associated with AFC were involved in superovulatory-related processes, such as regulation of primordial germ cells and cellular maintenance (Alward et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A population of antral follicles in a cow corresponds to the quantity of follicles present in the ovaries throughout the animal's life. The measurement of this parameter is carried out through the count of antral follicles (CFA) larger than 3 mm in diameter, which is performed by transrectal or transvaginal ultrasonography in female cattle (Alward et al, 2023). In this context, animals can be classified into high and low follicle counts.…”
Section: Antral Follicular Count (Afc's)mentioning
confidence: 99%